Pengaruh Hard Skill dan Soft Skill Terhadap Kesiapan Kerja Alumni Perbankan Syariah Pada Bank Syariah Melalui Motivasi Sebagai Variabel Intervening - Mahdi, Ilham; Rizal; Nofrivul (Al-bank: Journal of Islamic Banking and Finance, 2026)
This study aims to examine the effects of hard skills and soft skills on the work readiness of Islamic banking alumni, both directly and indirectly through work motivation as an intervening variable. A quantitative research design was employed using a census approach involving 196 alumni of the Islamic Banking Study Program at UIN Mahmud Yunus Batusangkar who had entered the workforce. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0.The results indicate that hard skills and soft skills significantly influence work motivation and work readiness. Soft skills demonstrate a stronger effect on work motivation, while motivation plays a crucial mediating role in strengthening the relationship between both types of skills and work readiness. Furthermore, work motivation significantly enhances graduates’ preparedness to meet professional demands, particularly in the Islamic banking sector. These findings contribute theoretically by reinforcing the role of motivation as a key mediating variable linking technical and non-technical competencies with work readiness. Practically, this study provides important implications for higher education institutions and the Islamic banking industry in designing curricula and development programs that integrate the enhancement of hard skills, soft skills, and motivational aspects to improve graduate employability and career alignment with the Islamic financial sector